KUALITAS PELAYANAN ADMINISTRASI PERTANAHAN DI KEMENTERIAN ATR/BPN KABUPATEN BANTAENG - Azizah, Nur; Mahsyar, Abdul; Azikin, Ruskin (Universitas Muhammadiyah Makassar, 2022)
The objective of this research was intended to find out the quality of the land administration servies on the ministry of national land affairs agency (ATR/BPN) of Bantaeng. The regulation number 12 of 2008 about local government which said that land service is the obligatory business which becomes the authority of local government is the business affairs of the district. The research method used a qualitative in case study method. The instrument of collecting data used interview, observation and documentation. The result of the research shaws that there were three thingss about this : (1) time precision of the service were according to the file needed in making certificate (2) the responsibility that given to the society was still low (3) the society has a low understanding eventhough the information access has been on hand.